Korean Red Ginseng suppresses bisphenol A-induced expression of cyclooxygenase-2 and cellular migration of A549 human lung cancer cell through inhibition of reactive oxygen species - Song, Heewon (J Ginseng Res, 2021)
BACKGROUND: Korean Red Ginseng (KRG) is a natural product with antiinflammatory and anticarcinogenic effects. We have previously reported that the endocrine-disrupting compound bisphenol A (BPA)-induced cyclooxygenase-2 (COX-2) via nuclear translocation of nuclear factor-kappa B (NF-κB) and activation of mitogen-activated protein kinase and promoted the migration of A549. Here, in this study, we assessed the protective effect of KRG on the BPA-induced reactive oxygen species (ROS) and expression of COX-2 and matrix metalloproteinase-9 (MMP-9) in A549 cells. METHODS: The effects of KRG on the upregulation of ROS production and COX-2 and MMP-9 expression by BPA were evaluated by fluorescence-activated cell sorting (FACs) analysis, quantitative reverse transcription polymerase chain reaction, and western blotting. Antimigration ability by KRG was evaluated by migration assay in A549 cells. RESULTS: KRG significantly suppressed the BPA-induced COX-2, the activity of NF-κB, the production of ROS, and the migration of A549 cells. These effects led to the downregulation of the expression of MMP-9. CONCLUSIONS: Overall, our results suggest that KRG exerts an antiinflammatory effect on BPA-treated A549 cells via the suppression of ROS and downregulation of NF-κB activation and COX-2 expression which leads to a decrease in cellular migration and MMP-9 expression. These results provide a new possible therapeutic application of KRG to protect BPA-induced possible inflammatory disorders.